A Multidisciplinary, Team-Based Teleconsultation Approach to Enhance Child Mental Health Services in Rural Pediatrics. Issue 3 (3rd July 2018) - Margolis, Kate; Kelsay, Kimberly; Talmi, Ayelet; McMillan, Heidi; Fraley, M. Cecile; Thomas, John F. Fred
ABSTRACT: Mental health services for rural youth are extremely limited, especially given the national shortage of child and adolescent psychiatrists (CAPs). Patient-centered primary care medical homes (PCMHs) are often their only available portal of care, yet high-quality PCMH integrated models of behavioral health that include a CAP are rare. This manuscript presents a unique multidisciplinary teleconsultation model wherein integrated behavioral systems consultation was employed to increase access to integrated behavioral health services. Common referrals included complex presentations outside of provider comfort range or medication and diagnostic clarification. Primary concerns were symptoms of ADHD, autism spectrum disorder, anxiety, and depression. Recommendations included referral to outpatient therapy, further coordination with the medical team, and follow-up with the CAP. Providers noted access to care, specialized quality of care, provider support, and enhancing principles of the PCMH as strengths of the teleconsultation. Challenges included patient engagement, scheduling/availability, challenges with the teleconsultation process, and provider-level barriers.